MICROMACHISMS OR MICRO VIOLENCE IN THE COUPLE: AN EMPIRICAL APPROXIMATION - Ferrer Pérez, Victoria A.; Bosch Fiol, Esperanza; Navarro Guzmán, Capilla; Ramis Palmer, M. Carmen; García Buades, M. Esther (Anales de Psicología / Annals of Psychology, 2008)
Research on attitudes about domestic violence has described negative attitudes to this violence, in general population and also in spe-cific collectives.In despite of this, we have less knowledge about behaviours consid-ered abusive by expert people (and that we permit us to describe technical violence or covert violence).This piece of work has like objective to evaluate attitudes to these covert forms of domestic violence (or micromachisms) and this social ac-ceptance. For this, we create a questionnaire with 25 items that has admin-istered by telephone to 1351 people.Results indicate that the questionnaire created is formed by five fac-tors that explaining 42.53% of total variance and evaluate attitudes to be-haviours from men to women in the couple like invasion of physical or symbolic spaces, make fear, relegate women to traditional feminine role, or to control or not value women. We analyse level of acceptance of this mi-cromachisms between interview people, in general and differentiated by gender and age.